Bioekologi Fitoplankton di Laguna Gampong Pulot (LGP) Kabupaten Aceh Besar - Syahrul Purnawan; Irma Dewiyanti; Teuku M. Marman (Omni-Akuatika, 2016)
The objective of the present study was to determine the diversity of phytoplankton and its relationship with physical-chemical water parameters of Gampong Pulot Lagoon, Leupung subdistrict, Aceh Besar. The collecting of phytoplankton and water quality were conducted in December 2014. According to field assessment, there were six stations to represent the study site. We recorded 25 species of phytoplankton from class Bacillariophyceae, Dinophyceae and Cyanophyceae. The abundance of Bacillariophyceae was 1202.02 ind / L classified as moderate, while Dinophyceae and Cyanophyceae were 621.13 ind / L and 208.49 ind / L, respectively, classified as low abundance. Bacillariophyceae was dominated by Rhizosolenia sp. with 26% of composition. The diversity index has varied from 1,88 to 2,63 indicated as moderate value.  Based on Principal Component Analysis (PCA) showed that the physical-chemical water parameters related to the abundance of phytoplankton in Gampong Pulot Lagoon.